2018
DOI: 10.3390/rs10101573
|View full text |Cite
|
Sign up to set email alerts
|

Ecosystem Services in a Protected Mountain Range of Portugal: Satellite-Based Products for State and Trend Analysis

Abstract: Mountains are facing strong environmental pressures, which may jeopardize the supply of various ecosystem services. For sustainable land management, ecosystem services and their supporting functions should thus be evaluated and monitored. Satellite products have been receiving growing attention for monitoring ecosystem functioning, mainly due to their increasing temporal and spatial resolutions. Here, we aim to illustrate the high potential of satellite products, combined with ancillary in situ and statistical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…eBird‐based models provided more accurate predictions for less common species (the narrow range) than Atlas data that recorded much more widespread species, with strong implications for species conservation. Our results also confirmed that model predictions benefit from the combination of macroclimate data and remote‐sensing‐derived EFAs, which has also implications for both conservation (Arenas‐Castro et al, 2019; Regos et al, 2020) and management (Carvalho‐Santos et al, 2018). Among other drawbacks, we also showed that there are important biases in model estimation as well as overconfidence about results accuracy or quality (e.g.…”
Section: Discussionsupporting
confidence: 81%
“…eBird‐based models provided more accurate predictions for less common species (the narrow range) than Atlas data that recorded much more widespread species, with strong implications for species conservation. Our results also confirmed that model predictions benefit from the combination of macroclimate data and remote‐sensing‐derived EFAs, which has also implications for both conservation (Arenas‐Castro et al, 2019; Regos et al, 2020) and management (Carvalho‐Santos et al, 2018). Among other drawbacks, we also showed that there are important biases in model estimation as well as overconfidence about results accuracy or quality (e.g.…”
Section: Discussionsupporting
confidence: 81%
“…Remote sensing techniques can be helpful in such cases and have been commonly used for this purpose [1][2][3][4]. Such studies mostly focus on estimation of canopy height since this is the most critical factor to predict risk [1,[5][6][7][8][9] but they also estimate other inventory parameters like tree basal area, volume (e.g., [3]) or ecosystem services [10]. The detection of individual trees in dense forests is also possible, driving the forest inventory from stand-and plot-level to single tree levels [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Long-term eco-restoration projects are critical in sustainable ecological and economic development [31,63,64]. Since the end of the 1990s, China has initiated specific ecological protection polices, such as the Grain for Green Project, the Beijing–Tianjin Dust Storms Sources Control Project, Grassland Ecological Protection Subsidy Incentives, and the Grain for Forage Project, with remarkable effects.…”
Section: Discussionmentioning
confidence: 99%